Evolução tectônica do Craton Amazonas na região Sudeste do estado do Amazonas: um estudo em múltiplas escalas com base na integração de dados geológico–estruturais e geofísicos - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
In the SW Amazonas State the plutonic-volcanic and sedimentary rocks were grouped in different petrotectonic associations: Juruena Basement (JBA), Juruena Supracrustal Suquence (JSSA), Post-Juruena Volcano-plutonism (PJVPA) and Post-Juruena Sedimentary Sequence (PJSSA). The JBA and JSSA (1.81–1.74 Ga), are arc magmatic-related, whereas the PJVPA (1.64–1.53 Ga) and PJSSA (1.74–1.08 Ga) define the main post-orogenetic events in this region. Magnetic data analysis show at least three patterns, named in relative chronologic, as deep linear anomalies with ENE-WSW trend (L0); linear shallow anomalies with NW-SE (L1) and NE-SW (L2) trends. The relationship of superposition suggests that L1 cross-cut L0, and both are transposed by L2 pattern. Geological-structural studies point out three structural styles, two them belongs to a NW-SE deformational belt: 1) D1 – banding folded structures from gneisses (upper amphibolite, 1.52 Ga); and 2) D2 – mylonitic foliation and schistosity structures in temperature of ~350ºC (greenschist, 1.48-1.46 Ga). The third structural style (D3) has ENE-WSW and NE-SW trends, well-defined cataclastic zones generated under temperature <350ºC (lower greenschist, 1.32 Ga). These structural styles have a correlation with main crustal reworking events of Rondônia-Juruena Provínce: a) L0 magnetic anomalies and S1 polydeformational lineaments - generated in the collisional event (1.64 Ga) responsible by Juruena magmatic arc and Tapajós-Parima continent amalgamation; b) L1 magnetic anomalies and S2 lineaments - related to the another collisional event (1.52 Ga), responsible by Tapajós-Parima and Juruena-Jamari terranes collage; c) L2 magnetic anomalies and S3 lineaments - related to Sunsás Orogenic Cycle, represented by Candeias Orogeny (1.37–1.32 Ga).
Keywords: Proterozoico; Arco Magmático Juruena; Cráton Amazonas; Proterozoic; Juruena Magmatic Arc; Amazonas Craton; CIÊNCIAS EXATAS E DA TERRA: GEOCIÊNCIAS